Genograms in family assessment - McGoldrick, Monica; Gerson, Randy (W.W. Norton & Company, 1985)
Widely used by both family therapists and family physicians, the genogram is a graphic way of organizing the mass of information gathered during a family assessment and finding patterns in the family system. Both entertaining and instructive, this book is the ideal way to introduce all those involved in family treatment to this essential assessment tool.
Keywords: Family; Behavioral Research; Family Therapy; rodina; psychoterapie; behaviorální výzkum; Famous Persons; významné osobnosti; rodinná terapie